2014
DOI: 10.1177/1074248414524302
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Anti-Xa in Pregnant Patients With Mechanical Prosthetic Valves Receiving Low-Molecular-Weight Heparin

Abstract: Anticoagulation with adjusted dose LMWH aimed to achieve guideline-recommended peak levels of anti-Xa for patients with MPHVs is commonly associated with subtherapeutic trough levels. Routine measurement of trough anti-Xa levels is therefore advisable in women with MPHV treated with LMWH during pregnancy to assure adequate level of anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…The measurement of trough levels may also be helpful, although data are scant. [153][154][155] In addition to anticoagulants, all pregnant women with mechanical valves should receive low-dose aspirin (75-100 mg once a day).…”
Section: Managementmentioning
confidence: 99%
“…The measurement of trough levels may also be helpful, although data are scant. [153][154][155] In addition to anticoagulants, all pregnant women with mechanical valves should receive low-dose aspirin (75-100 mg once a day).…”
Section: Managementmentioning
confidence: 99%
“…When used, UFH is adjusted to increase the activated partial thromboplastin time to two to three times the baseline. LMWHs are also usually dose adjusted to target peak anti-factor Xa (FXa) levels of 0.8 to 1.2 IU/mL 7,8 although some authors have suggested that levels of up to 1.5 IU/mL may be acceptable. 9 There are also increasing calls to use trough anti-FXa levels (0.6-0.8 IU/mL) to guide therapeutic efficacy.…”
Section: Heparinsmentioning
confidence: 99%
“…9 There are also increasing calls to use trough anti-FXa levels (0.6-0.8 IU/mL) to guide therapeutic efficacy. [7][8][9] LMWH is preferred over UFH due to its more predictable anticoagulant effect as well as concerns over the increased risks of heparininduced thrombocytopenia and osteoporosis with UFH. 10 However, LMWH is expensive in some countries and cost may be important factor to consider for some women.…”
Section: Heparinsmentioning
confidence: 99%
“…Th e increasing use of LMWH (recommended by current guidelines but not yet offi cially indicated for the prevention of thrombosis of mechanical valves in the summaries of the drug characteristics) requires treatment with therapeutic doses, determined based on periodic monitoring of the anti-Xa activity (measurements of peak anti-Xa levels mandatory, it also being possible in specifi c cases to measure through anti Xa activity levels) [23][24][25][26][27][28][29].…”
Section: Concise Practical Recommendationsmentioning
confidence: 99%
“…More recent research suggests that along with peak anti-Xa activity there should also be monitored trough (lowest) levels of anti-Xa activity [24]. It is known that pregnant women receiving enoxaparin every 12h with peak anti-Xa levels of 0.7-1.2 U/ mL are associated with sub-therapeutic trough levels, with a pre-dose level of less than 0.6 IU/ mL in over 50% of cases [24][25][26][27].…”
mentioning
confidence: 99%